Implementation of Classical Chinese Philosophical Values to Contemporary Chinese Language Learning in Indonesia - Junaeny, Arini; Fatmawati, Fatmawati (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2025)
This study aims to explore how classical Chinese philosophical values can be integrated into Mandarin language learning in Indonesia. This research used qualitative approach, The data was collected through interviews and open questionnaire. The main technique used was semi-structured interviews with open-ended questions to gain in-depth understanding from participants. The informants consist of five university teachers in Indonesia, 5-7 years of teaching experience. Open questionnaire was distributed to students of Chinese study programs in Indonesia. The study reveals that the integration of Chinese philosophical values—particularly Confucianism, Taoism, and Legalism—into education in Indonesia occurs through both implicit and explicit approaches. Implicit implementation is more prevalent, where moral values such as ethics, justice, honesty, wisdom, trust, humanity, and respect are naturally embedded in daily learning interactions. Explicit implementation is primarily confined to specialized courses, such as Chinese literature, culture, and philosophy, where classical texts, proverbs, and case studies are used to teach philosophical concepts.